(untitled) (Eurasian Journal of Religious Studies, 2018)
The article deals with the digital culture and its impact on modern youth and their relationship with parents. The problem of the Internet’s influence on the changing nature of relations between parents and children has been raised. The phenomenon of digital generation causes a number of contradictious opinions. Some people may say that digital generation is living at the origins of the “fourth industrial revolution”, however others consider, the disease of the 21st century is digital dependence of young people. Analysis of the modern research of the digital generation is widespread in foreign, rather than in domestic science. Most studies in Kazakhstan in the field of generation have only focused on their peculiarities and impact of the Internet on them. It is necessary to develop a research methodology and perspective directions for the development of this issue in education. This topic seeks to discuss relationship between children and parents in the present day. Do we really see the generation gap? The authors are discussing the issue of the phenomenal occurrence of the prefigurative culture, about which the well-known American anthropologist Margaret Mead wrote in the 1970s and what the forecasts of this culture will come in the future. The statistical data of various sources, a comparative analysis of the youth of modern Kazakhstan and the youth of Europe is analyzed. Authors give examples of the risks and threats that modern youth face in the global Internet and which role play parents for “digital natives”.